Model Pemberdayaan Masyarakat Melalui Konsep Usaha Tani Perkotaan - Muhammad Iqbal Usman; Muhammad Hasan; Citra Ayni Kamaruddin; N Nurdiana; N Nurjannah (SOCIETAS, 2023)
This study was structured to examine the model of community empowerment through the concept of urban farming in the Orchid Women Farmer Group (KWT) in Bara-Barayya Village, Makassar District, Makassar City. This study aims to determine how effective community empowerment is in urban farming. This study was compiled using qualitative analysis and then described by descriptive writing method. Purposive sampling is a sampling method in this study. Informants in the study included the Orchid Women Farmer Group (KWT), agricultural extension workers and the Makassar City Food Security Service. The researcher describes the empowerment model in the community using the CIPOO model approach (content, input, process, output, and outcome). The results of the study show the community empowerment model if in that approach, there is an approach that has not been fulfilled. However, the results of empowerment in urban farming at the Orchid KWT, run effectively and are carried out as they should, so that people who participate in these activities will be more concerned in utilizing the surrounding resources and increasing community harmony in one area.